2002
DOI: 10.1002/bse.321
|View full text |Cite
|
Sign up to set email alerts
|

Environmental management of transnational corporations in India—are TNCs creating islands of environmental excellence in a sea of dirt?

Abstract: This paper discusses how and to what extent local environmental practices at affiliated units of transnational corporations (TNCs) are influenced by TNC headquarters (HQ). The study focuses on intra‐firm dynamics of what is termed ‘cross‐border environmental management’ of TNCs. The study documents that the environmental management of TNC‐affiliated units in India are strongly influenced by HQ's environmental policies and standards. However, it is found that there are deviations in local practices from intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 6 publications
0
26
0
3
Order By: Relevance
“…According to several recent studies, firms in the rapidly industrializing economies of Asia and Latin America are increasingly adopting more environmentally sound technologies, organizational practices, and performances, although patterns of corporate greening remain "patchy" (Jenkins 2000;Ruud 2002;Utting 2002). This article aims to improve current understanding of these dynamics, offering a more completely specified account of emerging patterns of corporate environmentalism in developing countries.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…According to several recent studies, firms in the rapidly industrializing economies of Asia and Latin America are increasingly adopting more environmentally sound technologies, organizational practices, and performances, although patterns of corporate greening remain "patchy" (Jenkins 2000;Ruud 2002;Utting 2002). This article aims to improve current understanding of these dynamics, offering a more completely specified account of emerging patterns of corporate environmentalism in developing countries.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In some cases, such as product responsibility, supplier relations and environmental aspects, they add additional aspects to what has been common in the Chinese context (cf. Ruud, 2002). Results from a 2006 survey revealed that Chinese respondents also thought that multinationals scored better than domestic companies with regard to aspects such as CSR, handling of customer complaints and environmental protection (Liu, 2007).…”
Section: ==============mentioning
confidence: 99%
“…A conceptual route from GRI's 'sustainability context' to 'context-based sustainability' has been made (McElroy and van Engelen, 2012), but the specification of context here is based on objective norms, standards and thresholds of a particular territory/culture; they (i.e., the criteria) are 'subjective' only in the sense of affiliation to a local area. Although the sustainability approach should be personalised in territories/cultures where norms, values and economic progress vary (Rock, 2002;Ruud, 2002), on the other hand, the responsible subjects (i.e., governing bodies) of the ad hoc sustainability actions should be identified. In other words, up to now it has ignored the context's architect/designer (i.e., the CGB) who, with his observation (first) and with his design (after), influences the context dynamics determining the viability and the well-being of stakeholders (Golinelli and Volpe, 2012).…”
Section: The Research Problem: a Brief Literature Review Between Actumentioning
confidence: 99%